2015
DOI: 10.1111/josi.12130
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Psychological Capacity for Action: The Empowering Effect of a Microfinance Programme on Women in Sri Lanka

Abstract: This work examines the effect of a microfinance intervention on psychological empowerment among women in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 31 publications
(39 reference statements)
2
63
0
4
Order By: Relevance
“…Training has the potential to contribute to a real sense of independence among recipients, by strengthening human capabilities and promoting actions that can change recipients’ future status. Although the results of training need to be interpreted with some caution due to the small sample size of people having received training in our research, several studies have shown the numerous benefits of having received some form of training (e.g., Eden & Aviram, ; Frese et al ., ; Hansen, ).…”
Section: Discussionmentioning
confidence: 97%
“…Training has the potential to contribute to a real sense of independence among recipients, by strengthening human capabilities and promoting actions that can change recipients’ future status. Although the results of training need to be interpreted with some caution due to the small sample size of people having received training in our research, several studies have shown the numerous benefits of having received some form of training (e.g., Eden & Aviram, ; Frese et al ., ; Hansen, ).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have been conducted on the gender of beneficiaries of a microcredit and the results showed that microfinance does improve the empowerment of women and reduced gender discrimination (Bernstein, 2009;Hansen, 2015;Bayai and Khide, 2016). Other studies have been conducted by several types of research on the impact of microfinance on the socio-economic policies of developing countries, to know: Hulme and Mosley (1996); Wright (2000); Morduch and Haley (2002); Khandker (2003); Mosley and Steel (2004); Gué rin and Doligez (2006); Duflos et al (2009) (cited by Smahi et al, 2012, p. 2) and Feuilherade (2013) and Marku and Balili (2016).…”
Section: Microfinance In the Literaturementioning
confidence: 99%
“…These data show the need for an economic growth, especially through micro-loans granted by MFIs to people excluded from the banking system. It should be noted that women, deprived of funding (Hansen, 2015) according to the literature, must be targeted by MFIs (they presented only 24% of the labor force in 2014 in Lebanon -World Bank Report, 2015) because their needs are enormous.…”
Section: The Lebanese Socio-economic Contextmentioning
confidence: 99%
See 2 more Smart Citations